Consequences of job mismatch - CHOI, Dain (KDI School, 2017)
This study explores the effects of education-job mismatch, skill-job mismatch, and major-job mismatch on job satisfaction as well as on turnover intention. Moreover, special attention is paid to differences in the labor effects of job mismatches among junior college graduates, university graduates, and postgraduates who are currently enrolled, completed, or graduated from a master''s or Ph.D. programs. The data used is based on 2014 Graduates'' Occupational Mobility Survey (2014GOMS1). Furthermore, the samples are restricted to following categories: employees aged 25-34, graduates from tertiary education, and wage workers currently employed. Major findings from the empirical results are as follows; 1) under-education and skill deficit have significantly positive impacts on job satisfaction but do not have any significant influences on turnover intention; 2) over-education and skill surplus have significantly negative effects on job satisfaction and positive effects on turnover intention; 3) employees who experience job mismatches with respect to the field of education are less likely to be satisfied with their jobs and do not have significant relationship with turnover intention. Furthermore, although the labor market effects of job mismatches do not vary much according to educational levels; there are two different outcomes. These are 4) under-education does not have significant impact on job satisfaction in the case of postgraduates; and 5) with respect to turnover intention, it has been found that postgraduates from master’s or doctorate programs tend to be more influenced by skill-job mismatch, while university graduates tend to be more affected by education-job mismatch. Likewise, the degree of influence of education, skill, and major mismatches on job satisfaction and turnover intention is different. Therefore, public policy formulations would need to consider not only education-job mismatch, but also skill-job and major-job mismatches, when dealing with the issue of job mismatches. Consequently, it would be proposed that Korean education and labor policy measures that aim to close the huge mismatch gap between their tertiary education outcomes and industry needs should consider these three distinct types of job mismatches simultaneously in order to align both fields better.
Thesis(Master) --KDI School:Master of Development Policy,2017